Vision-Based Material Tracking in Heavy-Plate Rolling. Issue 20 (2016) - Schausberger, Florian; Steinboeck, Andreas; Kugi, Andreas; Jochum, Martin; Wild, Daniel; Kiefer, Thomas
Abstract: Knowledge of the position and the material conditions, e.g. the temperature, of the plates during hot rolling is important for process control. In fact, a precise material tracking system may help to prevent problems during the production process. This paper deals with the tracking of the rotation of heavy plates before and after the lateral expansion phase. The presented approach estimates the orientation and the position of the plate moving on the roller table. Images captured by a thermographic camera are utilized to identify the edges of the plate within the field of view. The detected edges are fed into an optimization-based estimation of the angular and translational position of the plate. Measurements of a plate from an industrial rolling mill demonstrate that the proposed method is robust against disturbances from the harsh environment nearby the mill stand.